Characterization of the Italian recreational bottom longline fisheries through social media platforms - Vianson, Giorgio; Petetta, Andrea; Li Veli, Daniel; Lucchetti, Alessandro (Frontiers in Marine Science, 2025)
Marine Recreational Fishing (MRF) is an important socio-economic sector worldwide, yet data scarcity on MRF effort poses challenges in understanding and managing its effects and impacts on fish stocks. This study investigates the characteristics and impacts of the bottom longline employed by MRF in Italian Seas. Data was collected through social media platforms, providing a contemporary approach to monitoring recreational fisheries. Although this experimental approach faces issues such as incomplete data and biases, it represents a cost-effective tool to monitor fishing effort and bycatch. Through the analysis of 235 observations across 7 different Mediterranean geographical subareas, we identified two longline types i.e. shallow-set (SLLS) and deep-set longline (DLLS), characterized their fishing methods, target species, catch efficiency, and bycatch occurrences. Results indicated that while the recent Italian regulatory change that reduced the maximum number of allowed hooks per vessel from 200 to 100 has generated controversy among recreational fishers, it does not significantly affect catch abundance or species composition. Furthermore, the study revealed low bycatch rates, particularly for sensitive species, but highlighted vulnerabilities among demersal elasmobranchs species. Overall, the present study contributed to understanding the dynamics of marine recreational longlining and highlighted the need for improved data collection methods and ongoing monitoring for evidence-based policy decisions in the context of Mediterranean fisheries management.